The Role of Storytelling and Bible Story Discussion Learning Methods in Enhancing Material Comprehension and Its Implementation in Modern Life - Hendry Sinaga; Roshayati Harefa; Prima Hermanugerah (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2025)
In the world of education, it is necessary to study innovative learning methods to achieve better education. Without innovative and creative learning methods, the goals of Christian religious education cannot be achieved properly. Because the success of Christian religious education actually lies in the cooperation of teachers and students in maximizing the desired teaching. Learning to understand the contents of the Bible requires innovation and appropriate methods to produce good quality learning and be able to improve understanding of the material and its implementation in today's life. It is known that the author examines the role of storytelling and discussion learning in understanding the contents of the Bible for students and how to implement it in today's life. The objectives of studying the role of the storytelling learning method and discussion of Bible stories are (1) To see the significance of increasing students' understanding in understanding the contents of the Bible, (2) To evaluate the increase in students' ability to implement Bible stories in today's life. The results of direct observation research in class carried out in 2 research cycles can be concluded as follows: (1) Students' ability to understand Bible story material can be improved through storytelling and discussion learning models. In the pre-cycle, students' ability to understand the material was 15%, increasing in cycle I by 78%, while in cycle II it was 85%. Thus, the application of learning to understand Bible stories through storytelling and discussion learning methods is very effective in improving students' ability to understand the material presented by the teacher. (2) Students' learning achievements also increase after implementing learning through storytelling and discussion learning methods. This can be seen from the results of the percentage of learning completion, both during the mid-semester evaluation and the final semester evaluation.